The Factors Influencing E-Book User Satisfaction and its Impact on the Continuity of E-Book Use - Widhiatma, Triyasa; Liputra, Vincent; Setiowati , Rini (Jurnal Locus Penelitian dan Pengabdian, 2025)
This study aims to analyze the effect of Ebook Pricing, Perceived Usefulness, and Perceived Ease of Use on Satisfaction, as well as the effect of Satisfaction on Continuous Intention in Ebook use. Using a quantitative approach and SEM-PLS analysis technique, this study collected data from respondents who were active users of Ebooks. The results of the study show that Ebook Pricing, Perceived Usefulness, and Perceived Ease of Use have a positive and significant effect on Satisfaction. Additionally, Satisfaction has been shown to have a strong effect on Continuous Intent, indicating that the higher the user satisfaction, the more likely they are to continue using Ebooks. These findings confirm the importance of strategies to increase functional value, ease of use, and pricing that are aligned with user value perceptions in optimizing the Ebook user experience. This study also recommends that future research use a longitudinal approach and add psychological and social variables to expand understanding of technology adoption behavior.